Efecto de tres medios de cultivo en la propagación in vitro de Solanum chaucha Juz. & Bukasov - Díaz-Pillasca, Hermila Belba (2022)
Solanum chaucha is a native species of the high Andean regions of Peru, Cajamarca region, known as chaucha, a term that means precocious or early and resides due to its rapid development. Due to its value for being a native species, its conservation is necessary, which is why within the conservation methods the biotechnological field is presented through tissue culture in in vitro conditions, which favors the conservation of plant material in times long-term pathogen-free. The objective of the research was to evaluate the effect of three culture media on the in vitro propagation of Solanum chaucha. Solanum chaucha axillary buds were used that were previously disinfected with ethanol (70%) and sodium hypochlorite (1%), the buds were introduced into three culture media that presented combinations of growth regulators (Gibberellic Acid, Naphthalene acetic Acid, Acid indole butyric acid and Kinetin) and the shoot and root formation response was evaluated. Obtaining the best results with the culture medium added with 0.1 mg/L of Gibberellic Acid and 0.5 mg/L of Kinetin in the number of shoots and length of shoots, as well as in the number of roots and root length.